2007
DOI: 10.1124/mol.107.034538
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinase Is an Endogenous Signal Retaining the Nuclear Constitutive Active/Androstane Receptor (CAR) in the Cytoplasm of Mouse Primary Hepatocytes

Abstract: The nuclear receptor constitutive active/androstane receptor (CAR) is sequestered in the cytoplasm of liver cells before its activation by therapeutic drugs and xenobiotics such as phenobarbital (PB) and 1,4-Bis[2-(3,5-dichloropyridyloxy)]benzene (TCPOBOP) in mouse liver, the regulatory mechanism of which remains poorly understood. Given the finding that epidermal growth factor repressed PB activation of CAR-mediated transcription (Mol Pharmacol 65:172-180, 2004), here we investigated the regulatory role of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 29 publications
7
65
0
1
Order By: Relevance
“…This could indicate that in human primary hepatocytes EGF is acting as a negative regulator of PB-mediated gene expression, which is similar to reports in primary hepatocytes in the rat (Kawamura et al 1999) and mouse (Koike et al 2007). …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This could indicate that in human primary hepatocytes EGF is acting as a negative regulator of PB-mediated gene expression, which is similar to reports in primary hepatocytes in the rat (Kawamura et al 1999) and mouse (Koike et al 2007). …”
Section: Discussionsupporting
confidence: 75%
“…In primary rat hepatocytes, Egf has been reported to inhibit PB-induced Cyp2b1/2 mRNA, while Hgf did not (Kawamura et al 1999). However, in mouse primary hepatocytes both Egf and Hgf appear to be inhibitory to the PB response (Koike et al 2007). It would be interesting to interrogate this system further and establish the effect of growth factors on Cyp2b1/2 expression in this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more work is needed to establish the molecular mechanism by which threonine 38 can be dephosphorylated after PB treatment. Recently, the growth factor-MEK-ERK1/2 pathway has been characterized as a cellular signal to sequester CAR in the cytoplasm; the inactivation of ERK1/2 by the MEK inhibitor U0126 spontaneously accumulates CAR in the nucleus of mouse primary hepatocytes (13). Our recent study has found that ERK1/2 specifically interacts with the phosphorylated form of CAR (data not shown), suggesting that ERK1/2 may be a signal that enables CAR to be phosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence, however, has suggested that the underlying mechanism should be a cell signal-mediated regulation; protein phosphatase 2A, for instance, may be involved in the PB-induced nuclear translocation in the mouse hepatocytes (11,12). Moreover, growth factors, such as epidermal growth factor and hepatocyte growth factor, repress CAR nuclear translocation, and the U0126 inhibition of the MEK-ERK pathway spontaneously translocated CAR into the nucleus and activated the target gene Cyp2b10 without drug exposures (13). Neither the type of kinase that phosphorylates CAR nor the residue of CAR that can be phosphorylated by this kinase, however, has been identified to this time.…”
mentioning
confidence: 99%
“…How is this dephosphorylation regulated? First, investigators found that growth factors such as EGF, hepatocyte growth factor, and insulin repress CAR activation and nuclear translocation in rat and/or mouse primary hepatocytes (Bauer et al, 2004;Koike et al, 2007;Yasujima et al, 2016). Therefore, CAR is, in principle, a cell signal-regulated nuclear receptor (Fig.…”
Section: Phenobarbital Induction Mechanismmentioning
confidence: 99%